Globalisation and new politics of micro-movements - Sheth, D.L. (2004)
In the process of opposition of globalisation, micro-movements have begun to raise a new discourse on democracy and invent political practices, expanding the arena of politics beyond the representational institutions of elections and political parties. They see globalisation as undermining and de-legitimising institutions of democratic governance and as a force which seeks to undo India's democratic revolution. This paper analyses the discourse and politics of micro-movements and their role in reinventing participatory democracy as a form of social action and political practice, creating new spaces and infusing deeper meaning to democracy in the globalising world. - Reproduced.
Keywords: Globalization